2014
DOI: 10.3390/nu6115312
|View full text |Cite
|
Sign up to set email alerts
|

Food Addiction and Its Impact on Weight-Based Stigma and the Treatment of Obese Individuals in the U.S. and Australia

Abstract: It is argued that food addiction explanations of obesity may reduce the significant stigma levelled at obese and overweight individuals. We surveyed 479 adults to determine the prevalence of food addiction in the U.S. (n = 215) and, for the first time, in Australia (n = 264) using the Yale Food Addiction Scale (YFAS). We also assessed the level of weight-based stigma in this population. The prevalence of food addiction in our Australian sample was 11%, similar to U.S. participants and consistent with previous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(16 citation statements)
references
References 34 publications
0
15
1
Order By: Relevance
“…As it relates to the other measures of weight stigma, such as weight‐based stigma towards a fictional character, perceived weight‐related teasing and fat stereotypes, Lee, Hall, Lucke, Forlini, and Carter () found no significant associations between weight‐based stigma towards a fictional character and a diagnosis of food addiction among adults. No significant association between implicit self‐discrimination and eating disorders has been reported among adults (Rudolph & Hilbert, ).…”
Section: Resultsmentioning
confidence: 99%
“…As it relates to the other measures of weight stigma, such as weight‐based stigma towards a fictional character, perceived weight‐related teasing and fat stereotypes, Lee, Hall, Lucke, Forlini, and Carter () found no significant associations between weight‐based stigma towards a fictional character and a diagnosis of food addiction among adults. No significant association between implicit self‐discrimination and eating disorders has been reported among adults (Rudolph & Hilbert, ).…”
Section: Resultsmentioning
confidence: 99%
“…Other groups included bariatric weight-loss groups (n = 6) (15,22,37,56,61,65) , undergraduate/students (n = 7 studies) (5,35,68,71,74,80,81) and disordered eating groups (n = 7) (17,43,47,49,50,64,73) . Fifteen studies included a population group other than Caucasian; however, other population groups such as African American or Hispanic were often in the minority and constituted <35% of the total study population (5,8,22,24,34,35,39,41,44,47,48,55,58,60) . Fifty-two studies reported the weight status of the population group, with many doing so objectively through direct measures of height and weight (n = 20 studies).…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…Most studies were conducted in predominantly Caucasian populations. Fifteen studies included a population group other than Caucasian; however, other population groups such as African American or Hispanic were often in the minority and constituted <35% of the total study population (5,8,22,24,34,35,39,41,44,47,48,55,58,60) .…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…Studies using obese samples have obtained point prevalence rates between 34% (Ceccarini et al, 2015) and 40% (Meule et al, 2014); for university student samples point-prevalence is around 11% (Obregón et al, 2015). Epidemiological research further shows, that FA is more prevalent in women (Fattore et al, 2014), middle-aged and older individuals (Bowen et al, 2014; Flint et al, 2014), overweight/obese patients (Meule, 2012; Pedram et al, 2013; Lee et al, 2014), and in people of Black or Hispanic ethnicity or low socioeconomic status (Berenson et al, 2015). …”
Section: Introductionmentioning
confidence: 99%